Analysis of Water Droplet Interaction with Turbulent Premixed and Spray Flames Using Carrier Phase Direct Numerical Simulations. Issue 7 (19th May 2023) - Concetti, Riccardo; Hasslberger, Josef; Chakraborty, Nilanjan; Klein, Markus
ABSTRACT: Carrier-phase direct numerical simulations (DNS) of n-heptane/air combustion with water droplet injection are reported in this paper. The influence of water droplet injection has been analyzed for statistically planar gaseous premixed flames and spray flames where the fuel is supplied in the form of monodisperse fuel droplets. The effects of water injection in both types of flames are compared, including their sensitivities on the initial diameter of water droplets. The simulations are based on an Eulerian-Lagrangian-Lagrangian approach to consider the multi-phase interaction and the simultaneous effects of n-heptane and water droplets. It is shown that the two types of flames are different in terms of several aspects. In particular, the spray flames are characterized by lower temperatures, and their propagation speed is lower than for premixed flames. The main reason for these differences lies in the gaseous equivalence ratio experienced by the reaction zone. For the cases investigated here, where the overall equivalence ratio is unity, the spray combustion occurs under predominantly fuel-lean conditions. Furthermore, the flame temperature is influenced by the initial diameter of water droplets, which affects the strength of thermal expansion within the flame. This in turn influences the evaporation characteristics of both fuel and water droplets due to different residence times within the flame. Although the effects of water droplets on the combustion mode are dependent on the relative position within the spray flame, the net effect is a partial shift from non-premixed to premixed mode. At the same time, the spray combustion occurs under relatively fuel-richer conditions with water injection and these trends appear consistently in laminar and turbulent flows.